(3QSGdI LHd GdSeGbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s; (3aGVd Hf CHj GdMSf GdESQGFjdj GdScfOQj, GHf GdHQbGfjs
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce hLd PcQg hTcQJ bGFe GdMb CeQg Edi LejY Cgd GdMb HGdLHd GdWGgQ s
(3BNQgG (B:s
(3fUMJce ceG jLH Ydi GdOYGg GdGHQGQ dCNhGfge GdehMOjf GdGWgGQ hGdMeO ddg GdefRg YeG jYHQ HGdHUGFQ hGdGacGQ JeJ GdQSGdI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis